Debris flow assessment in the crocker range at Ulu Moyog and Bundu Tuhan, Sabah, Malaysia - Edgar jr. joe (2018)
Debris flows are quite common in Sabah especially in the mountainous area of the Crocker Range and they pose a great danger to the public. While the hazard posed by debris flow is enormous, their inventory and susceptibility assessment are still lacking in Sabah. In the absence of a proper study, the mitigation strategies to address the debris flow hazards appear to be carried out on an ad-hoc basis. Therefore, this study aims to determine the characteristics of debris flow, to assess the susceptibility level in a basin scale, and lastly to suggest appropriate mitigation strategies. The assessment was conducted by using various methods, which included fieldwork and data collection along the channel, calculation of flow discharge and velocity, analysis of material property based on soil investigation report, rainfall intensity-duration threshold analysis, and lastly susceptibility modelling at a basin scale by applying Frequency Ratio method in geographic information system environment. Two locations of well-known occurrence of debris flow at Jalan Penampang-Tambunan KM 38.80 (Ulu Moyog, Penampang) and Jalan Tamparuli-Ranau KM 83.90 (Bundu Tuhan, Ranau) were selected for the case study. The inventory showed debris flow characteristics as follows: The velocity is equivalent to 0.1 to 2.0 times the discharge, while the travel distance equals to about 3 times the height relief; the debris flow is of granular type which shows high kinetic energy and velocity, as well as shorter transportation distance and high sedimentation towards the deposition; the formation of debris flow involves liquefaction process which is controlled by low plasticity index of soil and higher moisture content, and; lower rainfall intensity-duration threshold of the debris flow ranges between 2.97 mm/h and 8.02 mm/h which is given by the equation of I=9.9D-0.52. On the other hand, the susceptibility analysis displayed that most of the study basin is covered by low debris flow susceptibility, in which the controlling factors are the distance to negative lineament, normalised difference vegetation index, and distance to stream. The mitigation strategies were proposed by using the combination of both active and passive measures.